1986
DOI: 10.1530/jrf.0.0760841
|View full text |Cite
|
Sign up to set email alerts
|

Role of conceptus secretory products in establishment of pregnancy

Abstract: Conceptuses produce steroids, prostaglandins, proteins and possibly other unidentified agents which may play a role in the establishment and maintenance of pregnancy. A key event in this process is protection of the corpus luteum (CL) from the luteolytic activity of prostaglandin (PG) F-2 alpha of uterine origin. Oestrogens produced by the pig conceptuses between Days 11 and 16 appear to exert an antiluteolytic effect resulting in the sequestering of PGF-2 alpha within the uterine lumen. Failure of the pregnan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
56
0
2

Year Published

1989
1989
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(61 citation statements)
references
References 39 publications
3
56
0
2
Order By: Relevance
“…The results obtained suggested that the metabolism of 17α-hydroxyprogesterone, 20α-hydroxyprogesterone, 20β-hydroxyprogesterone and androgen did not differ between parthenogenetic and fertilized blastocysts, whereas the metabolism of progesterone and estrogen was lower in parthenogenetic blastocysts. Estrogen synthesized by embryos is thought to involve the transformation from morulae to blastocysts [25,26] and maternal recognition of blastocysts [27][28][29]. From the results of this study on estrogen metabolism, it can be concluded that the functions [25][26][27][28][29] mentioned above are low in parthenogenetic embryos, and that the low potential of development in parthenogenetic embryos is due to their low estrogen metabolism, in addition to the previous findings [1-3, 5-8, 18-24].…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The results obtained suggested that the metabolism of 17α-hydroxyprogesterone, 20α-hydroxyprogesterone, 20β-hydroxyprogesterone and androgen did not differ between parthenogenetic and fertilized blastocysts, whereas the metabolism of progesterone and estrogen was lower in parthenogenetic blastocysts. Estrogen synthesized by embryos is thought to involve the transformation from morulae to blastocysts [25,26] and maternal recognition of blastocysts [27][28][29]. From the results of this study on estrogen metabolism, it can be concluded that the functions [25][26][27][28][29] mentioned above are low in parthenogenetic embryos, and that the low potential of development in parthenogenetic embryos is due to their low estrogen metabolism, in addition to the previous findings [1-3, 5-8, 18-24].…”
Section: Discussionsupporting
confidence: 58%
“…Estrogen synthesized by embryos is thought to involve the transformation from morulae to blastocysts [25,26] and maternal recognition of blastocysts [27][28][29]. From the results of this study on estrogen metabolism, it can be concluded that the functions [25][26][27][28][29] mentioned above are low in parthenogenetic embryos, and that the low potential of development in parthenogenetic embryos is due to their low estrogen metabolism, in addition to the previous findings [1-3, 5-8, 18-24]. In the present study, however, there were many parthenogenones with low metabolism of estrogen and progesterone, even those developed into blastocysts.…”
Section: Discussionmentioning
confidence: 99%
“…The present results show that ER (and PR) disappear from the LE and are reduced in the GE and stroma in the mare, much like that shown for ruminants. Perhaps this explains the inability of exogenous oestrogen to lengthen luteal lifespan in mares as shown for pigs (see Bazer et al 1986). …”
Section: Discussionmentioning
confidence: 98%
“…Communication between the maternal uterine environment and the embryo is known to be vitally important to the establishment of pregnancy in normally cycling ewes and is mediated via secretions from both the endometrium and the embryo (Bazer & Roberts, 1983;Bazer et al, 1986). As yet we have no information on the biochemical nature of the endometrial/ conceptus secretions in the early post-partum ewe but it is possible that abnormal or asynch¬ ronous bi-directional signalling between them may be contributing to pregnancy failure in…”
Section: Discussionmentioning
confidence: 99%